2005
DOI: 10.1007/s10522-005-4901-4
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and Telomerase Biology in Vertebrates: Progress Towards a Non-Human Model for Replicative Senescence and Ageing

Abstract: Studies on telomere and telomerase biology are fundamental to the understanding of human ageing and age-related diseases such as cancer. However, human studies of whole body ageing are hampered by the lack of suitable fully reflective animal model systems, the wild-type mouse model being unsuitable due to differences in telomere biology. Here we summarise recent data on the biology of telomeres, telomerase, and the tumour suppressor protein p53 in various animals, and examine their possible roles in replicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 148 publications
2
33
0
Order By: Relevance
“…A couple of research groups have demonstrated that most somatic cells derived from pigs, unlike human somatic cells, are known to possess endogenous telomerase activity [47,48]. However, recent reports have also demonstrated that endogenous telomerase activity was shown to be restricted in the particular tissues/organs of pigs, and introduction of hTERT failed to reconstitute telomerase activity in the cells derived from pig [30,49,50]. These results suggest that telomerase activity might be required for cellular immortalization in the pig cells, depending on cell types, tissue origins or culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of research groups have demonstrated that most somatic cells derived from pigs, unlike human somatic cells, are known to possess endogenous telomerase activity [47,48]. However, recent reports have also demonstrated that endogenous telomerase activity was shown to be restricted in the particular tissues/organs of pigs, and introduction of hTERT failed to reconstitute telomerase activity in the cells derived from pig [30,49,50]. These results suggest that telomerase activity might be required for cellular immortalization in the pig cells, depending on cell types, tissue origins or culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of biological markers could complement clinical approaches facilitating risk prediction, early and accurate diagnosis, and monitoring newly developed treatments [1]. Telomere length is emerging as an important mechanism in vascular aging and, consequently, in the pathogenesis of hypertension, atherosclerosis, and heart failure [2][3][4][5][6][7] and represents a potential biomarker. Telomeres are essential elements consisting of non coding repetitive DNA sequences and binding proteins, located at the ends of chromosomes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the genetic interventions by transient or permanent transfection and ectopic expression of various genes on this model system have focused on extending the replicative lifespan of cells by bypassing the cell cycle check-points (Campisi and d'Adda di Fagagna, 2007;Collado et al, 2007). One of the most widely used genetic interventions in indefinitely extending the replicative lifespan of normal cells has been the ectopic expression of telomerase in a wide variety of cells (Simonsen et al, 2002;Davis and Kipling, 2005). However, continuous proliferation by such genetically modified non-aging cells often leads to their genomic instability, transformation, and cancer-forming activity (Wang et al, 2000;Serakinci et al, 2004).…”
Section: Gene Therapymentioning
confidence: 99%